Peningkatan Karakter Peserta Didik Berbasis Projek Profil Pelajar Pancasila di SMPN 12 Gorontalo - Patuti, Sri Mulyani; Adhani, Yuli; Yunus, Rasid (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2023)
AbstractThe improvement of student behavior that contradicts the values of Pancasila has become one of the challenges frequently encountered in the field of education. This issue needs to be promptly addressed by the government to safeguard the nation's continuity. The Minister of Education of the Republic of Indonesia has proposed the Pancasila Student Profile Project as an effort to cultivate students who embrace and apply Pancasila values. This research aims to understand the urgency of the Pancasila Student Profile and its implementation in enhancing the character of students at SMPN 12 Gorontalo. The research method employed is qualitative descriptive, utilizing data collection techniques such as observation, interviews, and documentation. The research findings indicate that the urgency of the Pancasila Student Profile at SMPN 12 Gorontalo lies in its role as a framework for 21st-century character and competencies. The implementation of the Pancasila Student Profile at SMPN 12 Gorontalo encompasses the development of dimensions related to faith, devotion to the One and Only God, and noble behavior; the dimension of cooperation; the dimension of critical thinking; and the dimension of creativity.————–AbstrakPeningkatan perilaku peserta didik yang bertentangan dengan nilai Pancasila menjadi salah satu tantangan yang kerap terjadi pada dunia pendidikan. Hal ini harus segera diselesaikan oleh pemerintah untuk menjaga kelangsungan bangsa. Menteri Pendidikan RI telah mengusulkan Projek Profil Pelajar Pancasila sebagai upaya untuk menciptakan peserta didik yang menganut dan menerapkan nilai-nilai Pancasila. Penelitian ini bertujuan untuk memahami urgensi Profil Pelajar Pancasila dan bagaimana implementasinya dalam meningkatkan karakter peserta didik di SMPN 12 Gorontalo. Metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa urgensi Profil Pelajar Pancasila di SMPN 12 Gorontalo adalah sebagai kerangka karakter dan kompetensi abad ke-21. Implementasi Profil Pelajar Pancasila di SMPN 12 Gorontalo meliputi pengembangan dimensi beriman, takwa kepada Tuhan Yang Maha Esa, dan berperilaku mulia; dimensi gotong royong; dimensi berpikir kritis; dan dimensi kreativitas.